Cellular identity through the lens of direct lineage reprogramming - Falk, Sven; Han, Dandan; Karow, Marisa (Current Opinion in Genetics & Development, 2021)
Direct lineage reprogramming challenges our traditional view on basic aspects of cellular identity, and in particular on processes crucial for identity acquisition. This is partly because in direct lineage reprogramming but not during natural differentiation processes changing cellular identity can occur in the absence of mitosis. Only recently, technologies emerged to deconstruct the cellular and molecular processes governing the transitory states a cell passes through on the journey from its original identity to the new target cell fate. Here we discuss arising concepts on the nature of these transitory states and the challenges and decisions cells must conquer to reach their new cellular identity.
CRIS-Team Scopus Importer:2021-08-20